LEGAL RESPONSIBILITIES AND ACCIDENTS IN PHYSICAL ACTIVITIES, IMPLICATIONS FOR PHYSICAL EDUCATION TEACHERS AND COACHES IN ILORIN METROPOLIS - Ajeigbe, Yaqub Issa (PEOPLE: International Journal of Social Sciences, 2016)
Laws are made for the general public in order to guide the people in their general behavior and attitude. When laws are enacted, they become the guiding principles that regulate our daily activities. Without the law there can’t be sin or sanctions. Therefore, in every aspects of our daily life there are implications guided by law. However, physical educators, sports coaches and administrators have become increasingly concerned about the legal implication of injuries that occur while students are receiving instructions during physical activities or sports programmes. Therefore, physical educators and coaches are subject to suit and may possibly have to pay damages when they have acted imprudently or unreasonably. They may also be vulnerable to suit when they fail to act in a situation where action could reasonably have been expected and where appropriate action probably would have prevented injury. Attention was given to probable causes of accidents during physical education lesson. The study is a descriptive survey and the population for the study comprised all the physical educators and coaches in Ilorin metropolis. Purposive sampling technique was employed to select 40% of the respondents and a total 100 male and female respondents out of 250 physical educators and coaches in the study area were used. Three research hypotheses were generated and structured questionnaire were used to collect data from the respondents. Inferential statistic of t-test was used to determine the significant factors of independent variables. The result shows that when physical educators/coaches are negligent in the performance of their duties or assumption of risk can make them to be held liable for any injury. Among the recommendation suggested include; physical education teachers, and coaches should be knowledgeable about the legal responsibility for students injures that will guide them in planning and execution of their daily duties among others.